The functional significance of vascular DNA hypermethylation in atherosclerosis: a historical perspective - Silvio Zaina (Frontiers in Pharmacology)
A decade ago, independent mechanistic and descriptive epigenomics data demonstrated for the first time that vascular DNA hypermethylation is a landmark of and causal factor in human and murine atherosclerosis. Since then, a flurry of converging evidence has assigned a prominent role to vascular DNA hypermethylation across the natural history of cardiovascular disease (CVD), from the exposure to risk factors, to the onset and progression of the atheroma. DNA hypermethylation is induced by and mediates the metabolic outcomes of high-fat diets and CVD risk-enhancing lipids in several models. Early-stage atheroma DNA is hypermethylated compared to normal adjacent tissue, and that trend is amplified as the atheroma progresses. That evidence has resulted in a strong interest for epigenetic drugs in CVD. Crucially, the DNA methylation inhibitor azacytidine has been singled out as a potent guardian of the contractile, anti-atherogenic phenotype of smooth muscle cells (SMC). Those findings are gaining relevance, as the antiatherogenic effects of the anticancer drugs azacytidine and decitabine fit into the recently revived hypothesis that the atheroma is a SMC-driven cancer-like mass. Finally, this 10-year anniversary has been marked by the first report that nanoparticles loaded with a DNA methyltransferase inhibitor drug are anti-inflammatory and inhibit murine atherosclerosis. Exciting work lies ahead to assess whether DNA hypermethylation is a practical and effective target to prevent or cure human atherosclerosis.